Analysis of the Impact of Teacher Program Direktorat PSMK(SM3T Program) to Animo Learning Students in Biological Lessons In SMKN 1 Kintamani, Bali - Ervan Johan Wicaksana; Pramana Atmadja (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2018)
This analytic descriptive study aims to determine the impact of the accompanying teacher of the SM3T program towards on the learning interest of the students in biology subject at SMKN 1 Kintamani, Bangli, Province of Bali. Data collection methods with observation, questionnaires and interviews. Data were analyzed by quantitative descriptive. The results of the regression analysis between the presence of the accompanying teacher and the learning interest of the students in Biology subject get a determination value of 0.28. These data indicate that 28% of the learning interest of students at SMK 1 Kintamani is influenced by the presence of a companion biology teacher in the Direktorat PSMK program. Abstrak. Penelitian deskriptif analitik ini bertujuan untuk mengetahui dampak program guru pendamping Direktorat PSMK (Program SM3T) terhadap animo belajar peserta didik pada mata pelajaran biologi di SMKN 1 Kintamani, kabupaten Bangli, Propinsi Bali. Metode pengumpulan data dengan observasi, angket dan wawancara. Data dianalisis dengan deskriptif kuantitatif. Hasil analisis regresi antara adanya guru pendamping dengan animo belajar peserta didik pada mata pelajaran Biologi mendapatkan nilai determinasi sebesar 0,28. Data tersebut menenuntukkan bahwa 28% animo belajar peserta didik di SMKN 1 Kintamani dipengaruhi oleh adanya guru biologi pendamping pada program Direktorat PSMK. Kata Kunci: Guru Pendamping, Program Direktorat PSMK, Animo Belajar